Educación Científica, reflexiones y propuestas desde los feminismos - Camacho-González, Johanna Patricia (Revista Científica, 2020)
This article presents some reflections and proposals from feminisms for research in the area of ​​science education. This is a discussion about the main contributions of gender studies that can contribute favorably to the current discussion and situations in relation to the role of subjects in scientific education with the purpose of moving towards societies that overcome inequality and move towards social justice First, there are links between the research of gender studies and the teaching of science in recent years. Subsequently, the discussion focuses on three strategies that allow articulating and guiding the current discussion in relation to a scientific education with a gender perspective. Finally, some reflections are pointed out with the aim of generating new proposals and future projections.